2022
DOI: 10.1016/j.jceh.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Poor Outcomes after Recidivism in Living Donor Liver Transplantation for Alcohol-Related Liver Disease

Abstract: Statistical MethodsData are shown as mean (standard deviation), percentage, or median (25-75 interquartile range). The recidivism and nonrecidivism groups were compared using Fisher's exact test or the chi-square test for categorical data and Student's t test for parametric data or the Mann-Whitney test for nonparametric data. Kaplan-Meier survival curves

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…There were no studies that explored psychosocial consequences of alcohol consumption after LT. Eight studies presented the effects of substance abuse treatment, alcohol contracts and multidisciplinary addiction teams in the prevention or identification of alcohol relapse (Attilia et al, 2018; Choudhary et al, 2022; Donnadieu‐Rigole et al, 2019; Kimura et al, 2017; Lee et al, 2018; Magistri et al, 2019; Masson et al, 2014; Rodrigue et al, 2013). Two of these studies were prospective and random selection was not performed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no studies that explored psychosocial consequences of alcohol consumption after LT. Eight studies presented the effects of substance abuse treatment, alcohol contracts and multidisciplinary addiction teams in the prevention or identification of alcohol relapse (Attilia et al, 2018; Choudhary et al, 2022; Donnadieu‐Rigole et al, 2019; Kimura et al, 2017; Lee et al, 2018; Magistri et al, 2019; Masson et al, 2014; Rodrigue et al, 2013). Two of these studies were prospective and random selection was not performed.…”
Section: Resultsmentioning
confidence: 99%
“…The relapse rates ranged from 9.5% to 45% in studies that defined alcohol relapse as ‘any alcohol consumption after transplantation’, and from 5.8% to 33.3% in studies where alcohol consumption beyond a certain amount or frequency was considered a relapse. Two studies conducted in India reported the lowest alcohol relapse incidence rates (Choudhary et al, 2022; Saigal et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ACCELERATE-AH cohort, where biomarker testing was used to supplement assessment of alcohol relapse, the cumulative incidence of any relapse was 25% (95% CI 18%-34%) at 1-year and 34% (95% CI 25%-44%) at 3year post-LT, with the cumulative incidence of sustained alcohol use being 10% at 1-year (95% CI 6%-18%) and 17% at 3-year (95% CI 10%-27%) post-LT (258). Early onset (,1-year post-LT) and heavy patterns of alcohol use are associated with reduced post-LT survival (258)(259)(260) among patients transplanted for AH.…”
Section: Ltmentioning
confidence: 99%
“…Recurrent alcohol-associated cirrhosis occurring in 9% of biopsied patients and 2% of all transplants was responsible for approximately 20% of posttransplant deaths. Early onset (,1-year post-LT) and heavy patterns of alcohol use are associated with reduced post-LT survival (258)(259)(260) among patients transplanted for AH. Policy measures aimed at reducing alcohol use include taxation, reduced availability, and restricted promotion of alcoholcontaining beverages.…”
Section: Ltmentioning
confidence: 99%